INTERRUPTIONS AND OVERLAPS OCCURING IN AN INDONESIAN TELEVISION TALK SHOW INDONESIA LAWYERS CLUB – TV ONE - Jessica Hartono; Samuel Gunawan (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
This research aims to help people understand about turn-taking irregularities, overlap and interruption and why it occurs. The classification of interruption is based on the definition of the interruption from Wardhaugh (1985). The writer believes that interruption and overlap are caused by certain reasons. The writer is interested in observing interruption and overlap in “Indonesia Lawyers Club” because she wanted to know which parties in this show produced more number of interruptions and overlaps, especially in an interactive dialog. There are two parties in this dialog, namely host and guests/panelist. This study was a qualitative study; the writer got the data from the transcript, which she did it manually. The writer analyzed all interruptions and overlaps from the host an guests/panelists which occurred in this show and classified the reason. The writer wanted to find out what the common reason of interruption and overlap are in this study. To decide the reason of interruption and overlap the writer looked at the context of the discussion between the host and the guest/panelists. The writer found that interruptions occurred more than overlaps. The common reason was seeking of clarification, and the other reason was confirming, completing, breaking up, and showing agreement. From all of this reason the writer conclude that interruptions and overlaps in this talk-show were not violation.